2016
DOI: 10.1016/j.carj.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Incidentally Detected Idiopathic Misty Mesentery on Multidetector Computed Tomography: Can Obesity be the Triggering Cause?

Abstract: The results of the present study show that idiopathic incidental misty mesentery appearance has a significant prevalence. Also, the high body mass index of these patients and the growing evidence of obesity-induced inflammatory changes in adipose tissue are suggestive of an association between obesity and misty mesentery appearance on CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
(58 reference statements)
2
5
0
Order By: Relevance
“…Although the patients with MM were significantly older than those without in our study, mean age was 45.2±12.2 years, younger than age group of SM. Our data and study of Unlu et al 19 are alike regarding mean age of these patients. Since SM is associated with many diseases and risk factors, different diseases might effect different age groups in SM.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Although the patients with MM were significantly older than those without in our study, mean age was 45.2±12.2 years, younger than age group of SM. Our data and study of Unlu et al 19 are alike regarding mean age of these patients. Since SM is associated with many diseases and risk factors, different diseases might effect different age groups in SM.…”
Section: Discussionsupporting
confidence: 71%
“…In their study, Canyigit et al 20 suggested that nonspecific chronic inflammatory reaction in SM is triggered by independent factors that cause disturbances of proinflammatory and anti-inflammatory cytokines in mesenteric fat. We suggest that urine in perinephric and pararenal spaces may incite an inflammatory response by adipocytes causing SM-like changes in intraabdominal adipose tissue as defined in the previous study regarding obesity and MM 19 . We believe this might be pathogenetic mechanism for the cause of MM in patients with ureterolithiasis.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…They hypothesized that changes in the mesenteric adipose tissue in inflammatory states (MP) might be similar to T2D because inflammation has been recognized to play a role in pathophysiology of T2D. Unlu et al noted that people with idiopathic misty mesentery had high BMIs: 67.5% were classified as obese and 17.5% as overweight [ 44 ]. Misty mesentery is also considered to be an important CT sign indicating early stage of MP.…”
Section: Discussionmentioning
confidence: 99%
“…Phlebitis seldom if ever happens in ordinary cases of MP, but may in those with suspected IgG4-RD [ 42 ]. An emerging concept of the possible relationship between MP and obesity and/or T2D suggests that MP may be an inflammation exclusively involving the mesenteric adipose tissue [ 43 , 44 ]. Hence, we believe that mesenteric panniculitis would be the best umbrella term to encompass a spectrum of rare idiopathic diseases characterized by chronic and fibrotic inflammatory changes in adipose tissue of the mesentery.…”
Section: Discussionmentioning
confidence: 99%